Shared immune-inflammatory mechanisms between ulcerative colitis and periodontitis: a multi-omics analysis - Li, Hongjiao; Li, Peimin; Guo, Xiaofeng; Zhou, Yan; Ma, Shaowei; Gao, Xin (Frontiers in Immunology, 2025)
BackgroundUlcerative colitis (UC) and periodontitis (PD) are chronic inflammatory diseases with increasing evidence of bidirectional communication through the oral–gut axis. However, the immunological mechanisms underlying their co-occurrence remain largely unclear.MethodsWe conducted a bidirectional Mendelian randomization (MR) analysis to evaluate potential causal relationships between UC and PD. Transcriptomic data from public repositories were integrated to identify shared differentially expressed genes. Immune-related genes were further screened using three machine learning approaches. Enrichment analysis and immune cell infiltration profiling were performed to explore underlying mechanisms. A rat model combining UC and PD was established to validate key findings in vivo.ResultsMR analysis revealed a unidirectional causal effect of UC on PD. Among the intersected immune-related genes, CXCL6 was identified as a hub gene significantly upregulated in both UC and PD. It was associated with neutrophil infiltration and pathways related to chemokine signaling and mucosal barrier disruption. In a dual-disease rat model, CXCL6 expression was further elevated in colonic tissues compared to UC alone, aligning with aggravated epithelial damage.ConclusionOur study identifies a shared immune signature between UC and PD, highlighting CXCL6 as a pivotal mediator. These insights deepen understanding of oral–gut mucosal interactions and inform future biomarker and mechanistic studies.